Value Added Intellectual Coefficient dan Stock Return - Thomas Julianto; Yulius Kurnia Susanto (Jurnal Wira Ekonomi Mikroskil, 2017)
The purpose of the research is to obtain empirical evidence about the influence of human capital efficiency, structural capital efficiency, capital employed efficiency, return on equity, growth, market to book value, and price earnings ratio on stock return on listed companies in Indonesia stock exchange from 2011-2015. There are 42 companies selected as final sample and hypothesis tested by using multiple regression analysis. The result of the research shows that capital employed efficiency and growth affected stock return. On the other hand, human capital efficiency, structural capital efficiency, return on equity, market to book value and price earnings ratio did not affect stock return.